Attitude, Perception of Risk Behavior and Behavior Management Cyberbullying among Undergraduate Students Uttaradit Rajabhat University - Thanasupawat, Assoc. Prof.Boonmun; Sooksa , Withaya; Maprakhob, Sutapa (Journal of Dhamma for Life, 2024)
The purpose of this research was to study 1) Behavior in using online media 2) Attitude and perception of risky behaviors that affect being bullied 3) Dealing with online bullying behavior 4) Factors influencing the management of online bullying behavior and 5) To study the guidelines and measures to solve and prevent online bullying behaviors of undergraduate students at Uttaradit Rajabhat University. The sample group used in the study was undergraduate students in their first to fourth years at Uttaradit Rajabhat University in the first semester of the academic year 2024, totaling 360 people, using a purposive sampling method calculated from Taro Yamane’s formula. The research instrument was a questionnaire. Data were analyzed using a ready-made computer program. The statistical methods used were frequency distribution, percentage, mean, standard deviation, and multiple regression. The results of the study found that the majority of the sample were female, accounting for 38.60 percent, first year students accounting for 30.00 percent, had used online media in the past 6 months accounting for 100 percent, spent more than 4 hours per day using online media accounting for 63.10 percent, and used Facebook the most, accounting for 39.20 percent. They knew about cyberbullying, accounting for 98.60 percent, and had been bullied online, accounting for 54.40 percent, with 38.03 percent being bullied via Facebook. The most common form of bullying was trolling, accounting for 21.74 percent. Overall, their attitude toward bullying behavior was at a high level (x = 4.03, S.D. = 0.28). Overall, their perception of risky behavior was at a high level (x = 3.78, S.D. = 0.60). Overall, their management of cyberbullying behavior was at a high level (x = 3.78, S.D. = 0.37) and the factors of risk behavior perception (X2) and attitude towards bullying behavior (X1) have a statistically significant influence on the management of online bullying behavior at the 0.01 level with a multiple correlation coefficient of prediction equal to 36.90 percent (R2= 0.369), which can be written as a regression analysis equation as follows: Y = 2.085 + 0.031 (X2) + 0.066 (X1)